Beyond Mortality: Exploring the Influence of Plant Phenolics on Modulating Ferroptosis—A Systematic Review - Nemanja Živanović; Marija Lesjak; Nataša Simin; Surjit K. S. Srai (Antioxidants, 2024)
Ferroptosis is a recently discovered type of programmed cell death that is mechanistically different from other types of programmed cell death such as apoptosis, necroptosis, and autophagy. It is characterized by the accumulation of intracellular iron, overproduction of reactive oxygen species, depletion of glutathione, and extensive lipid peroxidation of lipids in the cell membrane. It was discovered that ferroptosis is interconnected with many diseases, such as neurodegenerative diseases, ischemia/reperfusion injury, cancer, and chronic kidney disease. Polyphenols, plant secondary metabolites known for many bioactivities, are being extensively researched in the context of their influence on ferroptosis which resulted in a great number of publications showing the need for a systematic review. In this review, an extensive literature search was performed. Databases (Scopus, Web of Science, PubMed, ScienceDirect, Springer) were searched in the time span from 2017 to November 2023, using the keyword “ferroptosis” alone and in combination with “flavonoid”, “phenolic acid”, “stilbene”, “coumarin”, “anthraquinone”, and “chalcone”; after the selection of studies, we had 311 papers and 143 phenolic compounds. In total, 53 compounds showed the ability to induce ferroptosis, and 110 compounds were able to inhibit ferroptosis, and out of those compounds, 20 showed both abilities depending on the model system. The most researched compounds are shikonin, curcumin, quercetin, resveratrol, and baicalin. The most common modes of action are in the modulation of the Nrf2/GPX4 and Nrf2/HO-1 axis and the modulation of iron metabolism.